Association of sleep quality and obesity among undergraduate students in the School Of Health Sciences in USMKK - Halim, Siti Maizatul Raihanah Nor (Universiti Sains Malaysia, 2024)
This study aimed to determine the association of sleep quality and obesity among undergraduate students in the School of Health Sciences at USMKK. A cross-sectional study involving 128 undergraduate students was conducted using the convenience sampling method. An online questionnaire in the form of Google Forms was distributed to the respondents, which included socio-demographic characteristics, anthropometry data, and the Pittsburgh Sleep Quality Index (PSQI). The anthropometry assessment was conducted before respondents answered the questionnaire. Of the 128 respondents, 88.3% of students had poor sleep quality. This study also found that 30.5% of students were obese based on body mass index (obese I, obese II). Also, it was found that 21.9% of students had higher waist circumference values, while 26.6% had higher waist-to-height ratios. Based on the study's objective, the association of sleep quality and obesity based on body mass index was tested using Pearson’s Chi-Square test, while the association of sleep quality and obesity based on waist circumference and waist-to-height ratio was tested using Fisher’s Exact test. Unfortunately, there was no statistically significant association between sleep quality and obesity based on BMI, WC, and WHtR. In conclusion, poor sleep quality is a major problem among students, and this can lead to a higher risk of weight gain and obesity. Thus, effective strategies and awareness were needed to improve university students’ sleep quality and combat obesity.